(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The maximum children in the age group of 10-11 years were watching T.V. every day and all respondents did watch T.V. but the frequency of watching T.V. varies. To check whether this is only seen due to data fluctuation, we framed a hypothesis and tested it with the help of Chi square test. Structured schedule was also developed for parents to collect data. It included background information of parents and parent’s view regarding T.V. advertisement, nutritional status and buying behaviour of their children. Seen that results related that maximum, 50 of parents were having an age group of 35 to 40 years, 31.67 fall in the age group of 30 to 35 years, few of them i.e. 5 percent were above 40 years of age, and 13.33 were below, 30 years of, age. Out of 60 of respondents of 40 were females and 20 were males. The personal profile of the respondents regarding their occupation showed that maximum parents are doing their own business. 26.67 were in government service, 20 were in private jobs, 8.33 are not working and doing some other occupation. The data shows that generally the trend of business is increasing, whether for males or for females. Results on the income of the family showed that maximum of them were earning 20 to 30 thousand Rs. per month. Very few of them almost 3.3 of them had a monthly income above 50000 Rs. It is clearly depicted that parents usually watch T.V. Ads and they even liked watching it but they strongly believed that it creates a solid negative impact on the mind of the students and change their behaviour to careless and uncivilized social beings.it had some positive impact also on the mind of Children such that it helps them learn many new technology, advancements, makes them materialistic, makes them react smarter and sensible.